Vibration Analysis of Typical Flat Plate Ship Structures Through a New Method - Shuo Li; Yuhang Tang; Jiangtao Liu; Haichao Li; Xuhong Miao (Journal of Marine Science and Engineering)
The structural vibration problem in ships and marine structures is one of the core issues in this field. The typical flat plate is a basic structural unit that constitutes the main structures of the hull, such as the cabin, bow and stern, double bottom, superstructure, etc. Typical plate structures and plate frame structures are the basic structures that researchers focus on. This article briefly reviewed the development history of vibration prediction methods for typical flat plate structures and carried out work inspired by different methods and ideas. In order to provide a new tool for predicting the vibration wave energy distribution of typical flat plate structures, a new method for predicting the vibration wave energy distribution of a simple flat plate structure is proposed. This method combines the ideas of ray tracing and the finite element method, discretizes the structure into elements, and represents the transmission of vibration in the structure in the form of energy function mapping between elements and boundaries. After sufficient mapping, the steady-state solution of structural vibration energy density can be obtained. Compared with the finite element method and ray tracing method, this method has better computational efficiency; compared with statistical energy analysis, this method has better spatial resolution.